Composite scaffolds for cartilage tissue engineering based on natural polymers of bacterial origin, thermoplastic poly(3‐hydroxybutyrate) and micro‐fibrillated bacterial cellulose. Issue 7 (19th April 2016) - Akaraonye, Everest; Filip, Jan; Safarikova, Mirka; Salih, Vehid; Keshavarz, Tajalli; Knowles, Jonathan C; Roy, Ipsita
Abstract : The compressive modulus and yield strength of the P(3HB)/MFC composite increased by 124.1% and 102% respectively, with respect to neat P(3HB), on addition of 40 wt% MFC. The physical characteristics of the composite resulted in optimal cell attachment, proliferation and maintenance of the chondrocytic phenotype. Abstract: Cartilage tissue engineering is an emerging therapeutic strategy that aims to regenerate damaged cartilage caused by disease, trauma, ageing or developmental disorder. Since cartilage lacks regenerative capabilities, it is essential to develop approaches that deliver the appropriate cells, biomaterials and signalling factors to the defect site. Materials and fabrication technologies are therefore critically important for cartilage tissue engineering in designing temporary, artificial extracellular matrices (scaffolds), which support 3D cartilage formation. Hence, this work aimed to investigate the use of poly(3‐hydroxybutyrate)/microfibrillated bacterial cellulose (P(3HB)/MFC) composites as 3D‐scaffolds for potential application in cartilage tissue engineering. The compression moulding/particulate leaching technique employed in the study resulted in good dispersion and a strong adhesion between the MFC and the P(3HB) matrix. Furthermore, the composite scaffold produced displayed better mechanical properties than the neat P(3HB) scaffold. On addition of 10, 20, 30 and 40 wt% MFC to the P(3HB) matrix, the compressive modulus was found to have increased by 35%, 37%, 64% and 124%, while the compression yield strength increased by 95%, 97%, 98% and 102% respectively with respect to neat P(3HB). Both cell attachment and proliferation were found to be optimal on the polymer‐based 3D composite scaffolds produced, indicating a non‐toxic and highly compatible surface for the adhesion and proliferation of mouse chondrogenic ATDC5 cells. The large pores sizes (60 ‐ 83 µm) in the 3D scaffold allowed infiltration and migration of ATDC5 cells deep into the porous network of the scaffold material. Overall this work confirmed the potential of P(3HB)/MFC composites as novel materials in cartilage tissue engineering. © 2016 Society of Chemical Industry